PERANCANGAN PROTOTYPE HAND GLOVE BERBASIS ARDUINO SEBAGAI ALAT BANTU IDENTIFIKASI OBJEK BAGI PENYANDANG TUNANETRA - Sun, Enrique Justine; Fajar, Mohammad; Munir, Abdul (STMIK KHARISMA Makassar, 2025)
Blind individuals face obstacles in identifying objects or things around them, so a tool is needed that can help overcome these obstacles. This study aims to design an Arduino-based Hand Glove prototype that can help blind people identify objects around them. Research data collection was carried out through literature studies and testing of the designed prototype. The system is designed to consist of two large parts, the first part is the hand glove used by blind individuals, consisting of Arduino, RFID reader and speaker. The second part consists of objects to be identified that have been given an identity label in the form of a RIFD Tag. The evaluation results show that the design prototype can read and identify objects such as chairs, tables, laptops, cellphones and PCs which are distinguished from the sound variations that have been set and defined using a buzzer as a notification tool.